Proceedings of the 5th International Conference on Language, Literature, and Education (ICLLE-5 2022) 2022
DOI: 10.2991/978-2-494069-85-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Types of Sarcasm in the Comment Column of Male Netizen on the Youtube Account of Sukmawati Soekarno Putri News Video

Abstract: This study to analyze and describe the types of sarcasm used by male netizens in the comments column of Detik.com's youtube about Sukmawati Soekarnoputri's speech. This type of research is a qualitative research using descriptive method. The data of this research is the speech of male netizens in the comments column of the Detik.com youtube account about Sukmawati Soekarnoputri's speech. The source of the data for this research was taken from the news video of the Detik.com youtube account about Sukmawati Soek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…The results of this study are also not in line with the results of Melawati's research (2021) that show some types of sarcasm, including illocutionary, lexical, and prefix sarcasm, but not propositional sarcasm. Nevertheless there are some previous studies that reported similarities to the current research, for example, the research conducted by Sitanggang and Ningsih (2022), Lestari and Juita (2022), Maula and Muhayani (2022), Bachtiar andHardjanto (2018), andPadmantri andSutrisno (2020). All of them similarly found propositional, lexical, Like -Prefix, and Illocutionary sarcasm.…”
Section: Discussionsupporting
confidence: 74%
“…The results of this study are also not in line with the results of Melawati's research (2021) that show some types of sarcasm, including illocutionary, lexical, and prefix sarcasm, but not propositional sarcasm. Nevertheless there are some previous studies that reported similarities to the current research, for example, the research conducted by Sitanggang and Ningsih (2022), Lestari and Juita (2022), Maula and Muhayani (2022), Bachtiar andHardjanto (2018), andPadmantri andSutrisno (2020). All of them similarly found propositional, lexical, Like -Prefix, and Illocutionary sarcasm.…”
Section: Discussionsupporting
confidence: 74%